Basal plane pyrolytic graphite modified electrodes: comparison of carbon nanotubes and graphite powder as electrocatalysts. - Moore, R; Banks, C; Compton, R (2004)
The oxidations of NADH, epinephrine, and norepinephrine are studied using carbon nanotube and graphite powder-modified basal plane pyrolytic graphite electrodes. Immobilization is achieved in two ways: first, via abrasive attachment of multiwall carbon nanotubes or graphite powder by gently rubbing the electrode surface on a fine quality paper supporting the desired material; second, via "film" modification from dispersing either graphite powder or nanotubes in acetonitrile and pipeting a small volume onto the electrode surface and allowing the solvent to volatilize. While electrocatalytic behavior of both types of nanotube-modified electrodes is shown, with enhanced currents and reduced peak-to-peak separations in the voltammetry in comparison with naked basal plane pyrolytic graphite, similar catalytic behavior is also seen at the graphite powder-modified electrodes. Caution is, therefore, suggested in assigning unique catalytic properties to carbon nanotubes.